(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
Papaya is among the main fruit species produced in Brazil, representing high socioeconomic importance in productive regions. Changes in production methodologies aim to meet market demands and sector sustainability. In this sense, the use of organic compounds has been successfully used in the production of seedlings. The objective of the study was to evaluate the potential use of different sources of organic material for the composition of substrates used in the production of papaya seedlings, identifying the effects on the emergence and development of plants. Therefore, the treatments were composed of different substrates, namely: T1 – Soil; T2 – 75% soil and 25% chicken litter; T3 - 75% soil and 25% earthworm humus; T4 - 75% soil and 25% tanned cattle manure. When evaluating the characteristics, it was found that substrates composed of the fractions of earthworm humus and cattle manure allowed increases in the characteristics of shoot length, number of leaves, leaf area and stem circumference, while the presence of chicken litter interfered negatively on all the variables studied. It was concluded that organic compounds have the potential to favor the production of papaya seedlings. In this sense, the composition of the substrate alters the emergence and development of papaya seedlings, and the use of a fraction of 25% of earthworm humus allows the formation of seedlings with greater vigor, while the use of chicken litter in this same proportion should be avoided.